KARAKTERISTIK DAN EKSPRESI DENDANG MUARO PETI DARI BERBAGAI INTERPRETASI PENDENDANG - Melisa Fitri Rahmadinata; Mahdi Bahar; Wilma Sriwulan (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT Muaro Peti is one of Minangkabau repertoire songs originally from Muaro Peti Village, Kapur IX Sub-district, Limapuluh Kota District, West Sumatera. Cultural geographically, this village is the part of darek area located in indigenous territorial of Luhak Nan Tigo, Minangkabau.This song expresses particular characteristics of melody which differs from general darek songs, especially the movement of melodic lines which tends to decrease; while dominantly, the other darek songs tend to have ascending melodic lines. If it’s viewed textually melodic, the uniqueness of this song is also visible from its garinyiak (thriller), layuak (glissando), and non-chordal tone (appoggiatura) which appears as variation in song’s melody. In western music, the concept of ornamental tone or melody variation is the part of ornamentation. Furthermore, in term of interval, Muaro Peti song has genuine pentatonic scale, while the other darek songs generally have pentatonic scale which is close to diatonic scale. The differences in melody and interval eventually result on every singer’s particular singing style or music expression in singing Muaro Peti.The major approach in this research entitled “Characteristics and Expressions of Muaro Peti Song from Various Interpretations of the Singers” was done by using the analysis of laboratory work through various audio recordings of Muaro Peti song as the primary data. In this research, the qualitative field research was used as secondary data because this research did not investigate performance expression, but it’s more focused on music expression interpreted by the singers in singing Muaro Peti song